Determinants of Stunting In Children Aged 6–59 Months In West Sulawesi Province: A Secondary Data Analysis of The 2022 Indonesian Nutritional Status Survey (SSGI) - Ainur Basirah Mulya; Laila Ulfa; Lili Indrawati; Faika Rachmawati (CV. Inara, 2025)
Introduction:Stunting remains a major public health concern in Indonesia, particularly in West Sulawesi Province, which continues to report a high prevalence. Stunting refers to a failure of linear growth in children under five years of age, primarily resulting from prolonged nutritional deficiency and repeated infections, especially during the critical window of the first 1,000 days of life. This study aimed to identify the determinants of stunting among children aged 6–59 months in West Sulawesi Province using secondary data from the 2022 Indonesian Nutritional Status Survey (SSGI). Methods: This was a cross-sectional study using secondary data from the 2022 SSGI. The study population consisted of 3,686 households with children aged 6–59 months in West Sulawesi. Data analysis was conducted using univariate, bivariate, and multivariate approaches to identify variables significantly associated with stunting. Results: The dominant factor associated with stunting among children aged 6–59 months in West Sulawesi Province is birth weight (OR: 3.369). Children with a history of low birth weight (LBW) are 3.3 times more likely to experience stunting compared to those without such history, after controlling for maternal education, sanitation (latrine ownership), and immunization status. Conclusion: Low Birth Weight (LBW) is a significant contributing factor to the increased risk of stunting in children aged 6–59 months. Therefore, it is recommended to implement targeted interventions focused on fulfilling nutritional needs, monitoring growth and development, providing early stimulation, and promoting exclusive breastfeeding. These measures are essential to prevent and address stunting early in children with a history of LBW.